THE PECULIARITIES OF THE FORMATION AND FUNCTIONING OF LOGISTICS FLOWS IN THE FURNITURE INDUSTRY - PAVLYKIVSKA, Olha; KAMYSHNYKOVA, Evelina; HALYNIAK, Lesia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
It is known that the reformatting of logistics has become a key challenge for Ukrainian enterprises. It is outlined the main logistical problems during wars, which include refusal to accumulate, change in storage conditions, difficulties with purchase of goods, complication of logistics operations. It is considered the logistical activities of the private enterprise "Husiatyn furniture factory "Elegant" (Ternopil region, Chortkivskyi district), in particular, a change of logistics chain supplying of the main raw material, upholstery fabric for furniture, since February 24, 2022. The efficiency of replenishment is characterized of the company’s car fleet in connection with the purchase of a cargo vehicle of a DAF car for the delivery of own products, primarily to the eastern and southern regions. The sales activity of the furniture factory "Elegant" was monitored in the section of three zones: West, Center and South. It is determined the sales share of each region in the total volume of sales of the furniture enterprise for the period from 2016 to 2021. It was established that the leading positions from the implemented sales belong to the Western region (46%) due to geographic location of the furniture factory. It was found that during the analyzed period, all the IV quarter of the year is the most effective in the regions. Such dynamics are inherent not only furniture companies. New Year and Christmas are the most favourite holidays for Ukrainians, but they are "hottest" time for shopping in Ukraine. Furniture products are not an exception. Just to prepare for the celebration of the New Year and Christmas consumers spend a significant part of the funds. It is analyzed the work of the Husiatyn furniture factory on a monthly basis since the beginning of the Russian invasion on the territory of our state. It is determined the critical periods and positive shifts in economic activity of a furniture company. After comparing the volume indicators sale of furniture products in physical and value terms according to similar months in January - September 2021 and 2022, we draw the conclusions about a real picture of the work of the furniture enterprise today.